A reliability of the 20kV distribution system of alur dua langsa substation based on transient electricity and section technique - M. Ary Kurnyawan; Solly Aryza; Amani Darma Tarigan (Jurnal Scientia, 2024)
PT PLN (Persero) ULP Dua Langsa is a unit located in the Aceh region with losses of 4-7%. This research aims to analyze the reliability of 20 kV medium voltage overhead lines (SUTM) based on SAIDI and SAIFI. Factors that cause losses include loss of electrical energy due to load imbalances using unbalanced electrical loads in each phase. One of the programs to reduce losses to overcome this problem is using the MPR load balancing method (Reducing Technical Losses from House Connections) on New Installs, with the increasing number of customers and increasing growth in kWH sales, it is very important to control losses from balancing the transformer load. Compared with the system provisions at PT. PLN (Persero) The two-langsa flow is 1.04 for SAIFI, while the SAIDI value is 2.12. The ASAI (Average Service Availability Index) value is categorized as not yet reliable because it exceeds the IEEE standard of 0.999271.